Fire fighter robot: Inovasi robot pemadam kebakaran dengan arduino uno dan sensor flame - APRILIANI PUTRI, SHEILA (Maliki Interdisciplinary Journal, 2025)
This article aims to explore the development and implementation of Arduino Uno-based Fire Fighter Robot equipped with Internet of Things (IoT) technology to deal with fire disasters. By utilizing a flame sensor for early detection and an IoT module for remote monitoring, this robot is designed to increase the effectiveness and safety of fire extinguishing. This technology allows the robot to automatically detect the source of the fire, move towards the location, and spray extinguishing agents. In addition, real-time data sent by the robot to the monitoring system provides the firefighting team with important information regarding field conditions, so that decision making can be done faster and more precisely. Another advantage of this robot is its ability to reach areas that are difficult for humans to access, such as narrow spaces or high-risk locations, thereby minimizing the risk to officers. In the long term, further developments may include the integration of artificial intelligence (AI) for smarter navigation, as well as the use of materials that are resistant to extreme conditions. With this advanced technology, the Fire Fighter Robot is expected to be a revolutionary step in managing fire emergency situations.